Representações sociais da doença mental. Estudo qualitativo com psicólogos e psiquiatras. - Martins, António (2018)
The aim of this work is to study the social representations of Psychiatrists, Psychiatrist Interns, Child Psychiatrists and Clinical Psychologists about mental health and mental illness. A qualitative and exploratory study was developed based epistemologically on social constructionism and theoretically on social representations. Through the course of the research 30 health professionals participated in a semi‑structured interview whose content was analysed by means of the NVivo 10 Programme. The results showed that the social representations of mental illness are heterogeneous, emphasizing operational, etiologic‑explanatory and relativist conceptions. Mental health is conceptualized by health professionals according to the flexibility, adaptation, functionality and the biopsychosocial well‑being of individuals. Implications of this study to the theoretical framework of social representations of mental health/illness are considered. || Este trabalho pretende conhecer as representações sociais de Psiquiatras, Internos de Psiquiatria, Pedopsiquiatras e Psicólogos Clínicos sobre a saúde e doença mental. É um estudo qualitativo de carácter exploratório, pontuado epistemologicamente pelo construcionismo social e teoricamente pelo quadro das representações sociais. Participaram 30 profissionais de saúde mental, tendo sido realizada uma entrevista semiestruturada que foi analisada quanto ao seu conteúdo – através do programa NVivo 10. Da análise dos resultados, salienta‑se que as representações dos profissionais quanto à conceptualização da doença mental são heterogéneas, destacando‑se conceções operacionais, etiológico‑explicativas e relativistas. A saúde mental é conceptualizada pelos profissionais de saúde em função da flexibilidade, adaptação e funcionalidade e do bem‑estar biopsicossocial dos indivíduos. Implicações do presente estudo para o quadro teórico das representações sociais da doença mental são consideradas.